Investigation of the Efficacy of Different Physiotherapy Methods for Neck Pain - SARI, ZÜBEYİR (TAYLOR & FRANCIS LTD, 2012)
Objectives: This study was carried out to compare the efficacy of mobilization, Kinesio tape [KT], and classic treatment methods in patients with neck pain. Methods: Sixty patients with neck pain were enrolled. The patients were divided into three groups with 20 patients in each, for classic therapy, classic therapy plus mobilization, and classic therapy plus KT administered respectively to the first, second, and third groups. Pain levels and effects of the pain on daily life were assessed, respectively, with a visual analog scale and neck disability index [NDI]. Results: Following the treatment, decreases were observed in pain and NDI scores in all three groups [P<0.001]. However, no significant difference was observed in the inter-group comparison [P>0.05]. While all three groups individually responded significantly to treatment, none of the groups superseded the others. Conclusions: The results of this study suggest that KT and mobilization may be helpful as an alternative treatment in neck pain. Multi-centered studies in which the efficacy of KT and mobilization can be compared more objectively would be beneficial.
Keywords: Neck pain; Kinesio tape; mobilization; RANDOMIZED CLINICAL-TRIAL; MANIPULATIVE THERAPY; MOBILIZATION